Rare case reports: A rarity? - Simi Thankappan; Sherin Nedumpillil; Valsa Thomas (Wolters Kluwer Medknow Publications, 2022)
The basic principle of science is to always think of the simplest explanation for a condition. But in post graduate training, distinguishing a rare case from a common case is a dilemma for the naïve clinician. Often the eager and enthusiastic resident trainees are more prone to fall into this "rare case phenomenon." Innumerable rare case reports in countless scientific journals may give the false impression to the budding trainee that uncommon cases are encountered every now and then. This article stresses on the importance of applying certain rules that can help in making the diagnostic process systematic and simpler. The chance of encountering rare cases are in fact rare and limited, wherreas in some circumstances, can diagnose life threatening conditions too.